Respuesta :

Answer:

(2,-1) ;  (-1,  4)   ; ( 5 , -6)

Step-by-step explanation:

-5x - 3y = -7

Put x = 2 ,     -5*2 - 3y = -7

                         -10 -3y = -7

                             -3y = -7 + 10

                             -3y = 3

                                y = 3/-3

                                y = -1

(2,-1)

Put x = -1 ;   -5 *-1 -3y = -7

                         5 - 3y = -7

                             -3y = -7 - 5

                             -3y = -12

                                y = -12/-3

                                y = 4

(-1,  4)

Put x =  5,  -5*5   -3y = -7

                          -25 - 3y = -7

                               -3y = -7 + 25

                               -3y = 18

                                  y = 18/-3

                                  y = -6

( 5 , -6)

ACCESS MORE